Uremic Pruritus and associated factors in Chronic Dialysis Patients: An Observational Study in Western Nepal - Kumar, Ajay; Subedi, Saujan; Maskey, Abhisek; Asim, Mohammad; Sathian, Brijesh; Neupane, Deepika (Birat Journal of Health Sciences, 2020)
Introduction: Pruritus is one of the well-recognized major skin derangements in patients with advanced renal failure and are usually without visible skin lesions. Only few studies have addressed this issue in Nepalese population. Objective:.The present study aims to identify the prevalence and associated factors of uremic pruritus in chronic dialysis patients in western Nepal. Methodology:A prospective observational study was conducted to include all chronic dialysis patients with uremic pruritus at the Manipal Teaching Hospital, Pokhara, Nepal over a period of one year (June 2018 and May 2019). Results: During the study period, a total of 59 patients were included in the study with mean age of 55.8±15.8years,of which 37 (63%) patients developed uremic pruritus. Statistically significant relationship betweenpresence of pruritus and pruritus severity with frequency of itching grade and sleep disturbance score among elderly (p=0.001) were observed The serum urea can predict uremic pruritus among elderly patients with a good diagnostic value. The multivariate analysis showed male gender, hypertension, elevated serum albumin and random blood sugarwere independent predictors of pruritus in patients undergoing chronic dialysis. Conclusions: Our findings demonstrate that higher proportion ofpatients undergoing chronic dialysis werediagnosed with uremic pruritus (63%) and occurrence of pruritus had association with frequency of itching grade and sleep disturbance score .The serum levels of urea may predict the occurrence of pruritus among elderly patients.Furthermore, a large multicenter study is warranted with longer follow up which may provide robust information on the burden of pruritus and its associated factors to guide appropriate management among elderly.